Comparative Analysis of Corneal Parameters Performed with GalileiG6 and OCT Casia 2 - Robert Mazur; Adam Wylęgała; Edward Wylęgała; Dariusz Dobrowolski (Diagnostics, 2023)
Backgrounds: To compare keratometry (Ks and Kf), astigmatism (Ast.), and the astigmatism axes (Ax.) of the posterior surface of the cornea; the total, central cornea thickness (CCT); and the thinnest corneal thickness (TCT) measured using two different measurement methods. Methods: Patients qualified for cataract surgery at the Chair and Clinical Department of Ophthalmology, Division of Medical Science in Zabrze, Medical University of Silesia, Katowice, Poland, were included in the study and monitored with the following two devices: OCT-CASIA2 and Dual Scheimpflug Analyzer GalileiG6. Our work was a randomized, prospective study in which compliance with the agreement of measurements between the devices was evaluated using the Bland–Altman method. Results: A total of 110 patients (62 females and 48 males) were examined. Overall, 100 eyes of patients that qualified for cataract surgery were enrolled in the study. No statistically significant difference was observed for Total-Ks and Total-Kf. A significant difference was observable for the following parameters: total Ks-ax, total Kf-ax, the total power of astigmatism, and in all parameters of the part of the cornea and corneal thickness (CCT and TCT). Conclusions: The measurements obtained using Casia2 and the Dual Scheimpflug Analyzer GalileiG6 were significantly different and not interchangeable except for total Ks and Kf.